Politeness Strategy Used By Clothes Vendors At Tradional Market Pasar Bojong - Rostiana, Heva (Journal of English Education Studies, 2021)
The aim of this research was to know the politeness strategy used by clothes vendor at traditional market Pasar Bojong. The method of this research is descriptive qualitative approach. This researcher conducted on April 2021. In collecting the data, the researcher used observation and interview. The researcher recorded 5 speech events and utterances of 5 different respondents as the populations and samples of this research. Interview used to support the data. The result of this research shows that language used by most of clothes vendors was Sudanese, and they tend to use negative politeness than positive politeness of Sudanese language.